Positive Muslims: a critical analysis of Muslim AIDS activism in relation to women living with HIV/AIDS in Cape Town - Ahmed, Abdul Kayum (University of the Western Cape, 2013)
Magister Artium - MA (Anthropology/Sociology) === This research critically analysed Muslim approaches to five women with HIV/AIDS in Cape Town focussing particularly on the approach of 'Positive Muslims' - an awareness-raising and support group for Muslims living with HIV/AIDS. The central question of this thesis dealt with the impact of the norms, values and practices of Cape Muslims on the approach of Positive Muslims to women living with HIV/AIDS. It is suggested that while norms and values articulated in religious texts inform the ideological approach of the organisation's AIDS prevention model. This is due to the pragmatic approach adopted by Postive Muslims which recognises that the articulated norms and values do not always conform to the practices of Cape Muslims. === South Africa